Histomorphometric evaluation of calcium phosphate bone grafts on bone repair - Guimarães,Karis Barbosa (2011)
Because of its biocompatibility and osteoconductive properties, calcium-phosphate cement has been used as bone surrogate. OBJECTIVE: The purpose of this study was to do a histomorphometric comparison of bone regeneration using hydroxyapatite biphasic ceramic, calcium-phosphate cement and autogenous bone graft. STUDY DESIGN: Prospective and laboratorial experiment. MATERIALS AND METHODS: Two 5mm in diameter cavities (left and right - test and control) were made in the parietal bone of 72 rats. The GI, GII, GIII and GIV test cavities were filled with calcium-phosphate cement, biphasic ceramic hydroxyapatite, autogenous bone graft and blood. The animals were killed at 30, 60 and 90 days and the specimens underwent histomorphometric analysis. RESULTS: The results showed that autogenous bone graft treated defects had significantly more new bone at 30 days compared to other test groups. Within 60 and 90 days, bone formation was more significant in the test groups GI, GII and GIII; GI and GII encompassed larger areas. Throughout the evaluation periods, GII tests showed more bone formation when compared to GI. CONCLUSIONS: Biomaterials depicted a significantly increase in bone content, when compared to autogenous bone graft, concerning bone regeneration